Sistem Informasi Ujian Mandiri dan Seleksi Penerimaan Mahasiswa Baru (PMB) AMIK Garut Berbasis Intranet - Topan Setiawan (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
Independent exam information system and selection of new students collage, designed with the aim of providing higher education institutions such as AMIK Garut in determining qualified prospective students. This information system was built using the Waterfall method which contains: identification, planning, analysis of user requirements, software and hardware, database design and interface programs, system implementation, and system maintenance. User requirements, software and hardware obtained from observations, interviews and literature studies based on business analysis results, using tools include: Use Case Diagrams, Activity Diagrams, Class Diagrams and Sequence Diagrams for system design. Whereas Entity Relationship Diagram (ERD) for relational database design. This information system is designed with an intranet-based concept using the CodeIgniter Framework, HTML markup language, PHP programming and MySQL database